Aspek Maqashid Asy-Syariah pada Pasien di Unit Perawatan Kritis - Asriyani; Suhermi; Christina Nur Widayati; Febrianto Dwi Putra Hadju; Purwono; Chanif; Rohmat Suprapto (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Caring for hemorrhagic stroke patients in the Critical Care Unit (ICU) requires not only intensive medical care but also a comprehensive ethical and spiritual approach, especially for Muslim patients. Hemorrhagic stroke is an emergency condition with a high mortality rate and a significant risk of spiritual distress during critical care. This study aims to analyze the application of the Maqasid Al-Shariah principles in nursing care for hemorrhagic stroke patients in the ICU as an effort to improve the quality of holistic care. The method used is a library research with a qualitative approach, through a review of scientific literature, Islamic bioethics, and relevant critical care nursing practices. The results of the study indicate that the integration of the Maqasid Al-Shariah principles—especially hifz an-nafs (protection of the soul), hifz al-aql (protection of the mind), and hifz ad-din (protection of religion)—can improve clinical and spiritual outcomes for patients, characterized by improved levels of awareness, reduced spiritual distress, and increased patient and family satisfaction. Spiritual interventions such as Quranic recitation and family collaboration have been shown to support psychological stability and ethical care, especially in the end-of-life phase. In conclusion, the application of Maqashid al-Shariah in ICU care for hemorrhagic stroke patients provides an ethical and spiritual framework that enriches critical care nursing practice and is recommended as a basis for developing Islamic value-based nursing protocols in Indonesia.